1981
DOI: 10.3758/bf03212037
|View full text |Cite
|
Sign up to set email alerts
|

Tonic immobility in Japanese quail can reduce the probability of sustained attack by cats

Abstract: In a two-choice experiment, cats (Felis domesticusi chose an active quail (Coturnix coturnix japonica) more often than a quail in tonic immobility (TI). In a second experiment, cats were individually presented with two active quail in an open field. Holding and biting by the cat, particularly about the neck, was necessary for inducing TI in a bird. Overall, the total time spent by a cat in stalking, attacking, and handling a bird was inversely related to the total time spent in TI by the bird. These results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
6

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(53 citation statements)
references
References 23 publications
0
47
0
6
Order By: Relevance
“…In poultry there are good indications that the freezing seen in the birds is related to an anti-predator response with birds showing a shorter freezing response being more prone to being killed by predators [142]. The situation in the pig is more complex, in the most common restraint test in the pig, the backtest, the piglet is put on its back and either restrained manually [82] or by means of a small weight [17], and it is hard to see how this situation directly relates to a predation situation.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In poultry there are good indications that the freezing seen in the birds is related to an anti-predator response with birds showing a shorter freezing response being more prone to being killed by predators [142]. The situation in the pig is more complex, in the most common restraint test in the pig, the backtest, the piglet is put on its back and either restrained manually [82] or by means of a small weight [17], and it is hard to see how this situation directly relates to a predation situation.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Indeed [141] showed that "death feigning" birds often took advantage of escape opportunities. Later Thompson et al [142] showed that TI in quail reduced the probability of the birds being predated by cats.…”
Section: Introductionmentioning
confidence: 99%
“…Tonic immobility has been observed to occur in species of several phyla, and possibly even in humans (Suarez & Gallup, 1979). Naturalistic observations reveal that a number of prey do exhibit tonic immobility when contacted by a predator (Armstrong, 1965;Hediger, 1955;Sargeant & Eberhardt, 1975), and recent laboratory evidence (Thompson, Foltin, Boylan, Sweet, Graves, & Lowitz, 1981)shows that tonic immobility in quail deters predation by cats. The adaptive significance of both freezing and tonic immobility becomes obvious when one considers that sounds emitted by prey can attract predators (Busnel, 1963) and that prey movement is often a necessary condition for eliciting and maintaining orientation and/or attack (Askew, Musimeci, Sloane, & Stephan, 1970;Burghardt, 1966;Curio, 1976;Drummond, 1979;Fox, 1969;Herzog & Burghardt, 1974;Kaufman, 1974;MacDonald, 1973;Sisk, 1963;Smith & Watson, 1972).…”
mentioning
confidence: 99%
“…A IT está presente no sono da maioria das espécies, em filhotes de mamíferos suspensos pelo dorso, no predador observando a presa, em vários animais em alerta ou que mimetizam elementos inanimados do ambiente; e em situações mais específicas, tais como a fêmea de muitas espécies durante a cópula 20,21 . Em muitos casos, a IT é "um recurso usado em uma etapa derradeira do comportamento defensivo, quando outras estratégias se tornam ineficazes à preservação da vida" 16,24,25 . A origem filogenética dos mecanismos fisiológicos envolvidos nas respostas comportamentais da IT não é conhecida.…”
Section: Introductionunclassified